Numerical Modeling of Non-Isothermal Compositional Compressible Gas Flow in Soil and Coupled Atmospheric Boundary Layer (Communications in Computational Physics, 2019)
Compositional gas flow in a heterogeneous porous medium and in the coupled atmospheric boundary layer above the porous medium surface is of interest inmany applications, which requires reliable numerical tools for modeling of very complex physical processes. But there are still many important effects which are very oftenignored in contemporary models of this flow. One of them is compressibility. So far, nomodels of non-isothermal compositional compressible gas flow in a porous mediumand in the coupled atmospheric boundary layer above its surface has been reportedin the literature. Therefore, we propose mathematical and numerical models for thedescription of the above scenario. In order to assess the reliability of our numericalmodel, we analyze its convergence by quantitative computational studies. We alsopresent several qualitative computational studies which present the dynamics of thenon-isothermal compositional compressible gas flow in free flow–porous medium flowinteraction.
Keywords: Compressible flow; non-isothermal flow; compositional flow; porous medium; free flow; coupling conditions.